Peningkatan Komitmen Organisasional Guru Melalui Penguatan Supervisi Kepala Sekolah, Kerjasama Tim Dan Kepuasan Kerja Guru - Hasanah, Yanah Uswatul; Harijanto, Sutji; Muharam, Hari (JURNAL MANAJEMEN PENDIDIKAN, 2024)
IMPROVING TEACHERS' ORGANIZATIONAL COMMITMENT THROUGH STRENGTHENING PRINCIPAL SUPERVISION, TEAMWORK, AND TEACHER JOB SATISFACTION This study aims to test and analyze the direct and indirect effects of principal supervision, teamwork, and job satisfaction on the organizational commitment of ASN Elementary School teachers in Cicurug District, Sukabumi Regency. This study was conducted using a survey method, path analysis, and SITOREM  analysis with a quantitative approach. The population in this study was 172 respondents, with the determination of the research sample using random sampling techniques obtained 121 respondents. The analysis technique of the collected data was carried out using descriptive statistical analysis, prerequisite analysis test and cytorem analysis. The results of the study showed that principal supervision had a positive effect on teacher organizational commitment, teamwork had a positive impact on teacher organizational commitment, job satisfaction had a positive effect on teacher organizational commitment, principal supervision had a positive impact on job satisfaction, teamwork had a positive effect on job satisfaction, principal supervision had an indirect positive impact on teacher organizational commitment through job satisfaction, and teamwork had an indirect positive effect on teacher organizational commitment through job satisfaction. Schools can strengthen principal supervision, teamwork, and job satisfaction to improve teacher organizational commitment.